PENGARUH KECERDASAN EMOSIONAL, DAN SELF EFFICACY TERHADAP KINERJA GURU MATEMATIKA - Julita, Susnaini; Herawaty, Dewi; Gusri, Sandra Alfi (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2019)
The research was purpose to understand the relationship between emotional intelligence self-efficacy and job performance math teacher. The method was conducted by survey research. The research sample were 80 teachers of teachers on the junior high schools as Kota Bengkulu. The sample was selected by simple random sampling. The data was collected through a Likert scale questionnaire technique. The statistical analysis for the data, we were applied path analysis. The results of this study were 1) there is direct effect of emotional intelligence towards job performance math teacher, 2) there is direct effect of self-efficacy towards job performance math teacher, 3) there is direct effect of emotional Intelligence towards self-efficacy.